2016
DOI: 10.1007/s00213-016-4213-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral acetate supplementation attenuates N-methyl D-aspartate receptor hypofunction-induced behavioral phenotypes accompanied by restoration of acetyl-histone homeostasis

Abstract: The signature behavioral phenotypes induced by acute and chronic regimen of NMDA receptor antagonists seemed to be attenuated by GTA. This study thus provides a therapeutic paradigm of using dietary acetate supplement in psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…We have recently demonstrated that the concentration of acetate, the SCFA predominantly produced by microbial fermentation of B-GOS ® 55 , increases in the plasma of male rats following the ingestion of this prebiotic 39 . Furthermore, acetate supplementation itself is not only associated with increased levels of NMDAR subunits 39 , but has also been shown to rescue the behavioural effects of NMDAR blockade in rats 40 . We now show that B-GOS ® intake also increases plasma acetate in female rats (Table 2 ), though GluN2A (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that the concentration of acetate, the SCFA predominantly produced by microbial fermentation of B-GOS ® 55 , increases in the plasma of male rats following the ingestion of this prebiotic 39 . Furthermore, acetate supplementation itself is not only associated with increased levels of NMDAR subunits 39 , but has also been shown to rescue the behavioural effects of NMDAR blockade in rats 40 . We now show that B-GOS ® intake also increases plasma acetate in female rats (Table 2 ), though GluN2A (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial fermentation of prebiotics, such as Bimuno TM galacto-oligosaccharides (B-GOS ® ), produces the short-chain fatty acids (SCFA) including acetate, butyrate, and propionate 35 , 36 , which themselves influence host physiology 37 . Importantly, the transport of acetate into glial cells is modulated by signal transmissions dependent on the NMDAR 38 , and acetate supplementation itself elevates brain NMDAR subunit levels 39 and rescues NMDAR hypofunction in rodents 40 . Circulating acetate is also an appetite suppressant 41 , and increased hepatic levels of its metabolizing enzyme, acetyl CoA carboxylase (ACC) has been associated with reduced weight gain in olanzapine-injected rats, following antibiotic administration 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study male rats (250–300 g) were gavaged with glyceryl triacetate (GTA, 1 g/ml, Sigma Aldrich, UK) at a final dose of 3 g/kg, or the same volume of water alone (control) daily for 3 weeks. The choice of GTA dose and control was based on a previous studies ( Singh et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fermentation of B-GOS has been shown to produce significant amounts of acetate, and moderate amounts of butyrate ( Grimaldi et al, 2016 , Grimaldi et al, 2017 ). Both of these SCFAs can have central effects, particularly at the epigenetic level where they both influence the expression of brain histone deacetylases (HDACs) ( Soliman et al, 2012 , Han et al, 2014 ), but a link between metabolic acetate and NMDARs has also been demonstrated ( Hirose et al, 2009 , Singh et al, 2016 ). In this regard, if acetate is involved in B-GOS ® mediated changes of NMDAR function, then direct acetate supplementation might be expected to have similar effects on central NMDAR levels as the prebiotic itself.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the researchers need, this method may offer more comprehensive information compared to commonly used methods for ion concentration measurements. Furthermore, IC units equipped with a splitter for dual ion detection (cations/anions including, small SCFA) provides researchers a means to quantify common ions and difficult SCFA which are altered in pathophysiological states (Christensen et al 1996;Comerford Sarah et al 2014;Drapeau and Nachshen 1988;Jiang et al 2013;Mashimo et al 2014;Perry et al 2016;Rappaport et al 1987;Singh et al 2016;Stocker et al 2015;Watchorn 1933;Yang et al 2006) with minimal sample volume. We anticipate that this new method will be useful to many research groups investigating SCFA and electrolyte concentrations and those effects on: water and electrolyte homeostasis, stroke, cardiovascular disease, hypertension, metabolic processes, cancer, and ethanol metabolism (Chapp et al 2014), to name a few.…”
Section: Perspectivementioning
confidence: 99%